Aplicación del valor el riesgo y valor en riesgo condicional al incremento en los costos de atención por diagnóstico de VIH en Colombia (2012 A 2023) (2024)
The healthcare system in Colombia, reformed by Law 100 of 1993, has shown improvements in health indicators, coverage, and financial protection. However, it faces financial and administrative challenges, such as the high number of enrollees in the subsidized regime and the rising costs due to the unification of premiums and the adoption of new technologies. This paper analyzes the financial risk associated with HIV morbidity using the methodologies of Value at Risk (VaR) and Conditional Value at Risk (CVaR), evaluating data from 2012 to 2023 to anticipate and mitigate financial risks in the health sector.